A novel long noncoding RNA, TMEM92‐AS1, promotes gastric cancer progression by binding to YBX1 to mediate CCL5. Issue 4 (12th January 2021) - Song, Shubin; He, Xuezhi; Wang, Jing; Song, Hongtao; Wang, Yimin; Liu, Yansong; Zhou, Zhengbo; Yu, Zhiyong; Miao, Dengshun; Xue, Yingwei
Abstract : Numerous studies have revealed that long noncoding RNAs (lncRNAs) with oncogene properties play vital roles in gastric cancer (GC). In this study, we aimed to elucidate the function of TMEM92‐AS1 in GC progression and to investigate its underlying mechanisms. TMEM92‐AS1 was filtered from the Gene Expression Omnibus database. GC tissues and adjacent normal tissues were used to detect the expression level of TMEM92‐AS1. MTT, colony‐formation assays, Edu, cell cycle, apoptosis and subcutaneous tumour formation assays were used to detect the role of TMEM92‐AS1 in cell function. RNA transcriptome sequencing was used to seek downstream target genes. Reverse transcription (RT)‐qPCR, western blot, RNA and chromatin immunoprecipitation assays were used to investigate the mechanisms involved. TMEM92‐AS1 was significantly overexpressed in GC tissues and correlated with poor overall survival and disease‐free survival. Furthermore, TMEM92‐AS1 promoted GC cell proliferation and migration in vitro and tumorigenic ability in vivo . RNA transcriptome sequence analysis revealed a potential downstream target gene, C‐C motif chemokine ligand 5 (CCL5), and a mechanistic study found that TMEM92‐AS1 regulated CCL5 by binding to the transcription factor Y‐box binding protein 1(YBX1), which has oncogene properties. In addition, TMEM92‐AS1 was found to be associated with peripheral blood leukocyte counts, especially neutrophils. Further investigation found that TMEM92‐AS1 may affect leukocytes via regulation of the expression of granulocyte colony‐stimulating factor in GC tissues. Our data provide an in‐depth insight into the mechanism behind the lncRNA TMEM92‐AS1, how it promotes GC progression and the possible mechanism in affecting peripheral leukocyte counts. Therefore, TMEM92‐AS1 is a potential target for GC individualized therapy and prognostic assessment. Abstract : Oncogene‐like effects of TMEM92‐AS1: LncRNA TMEM92‐AS1 regulates the expression of downstream target gene CCL5 by binding with YBX1 protein to play the role of oncogene and affects prognosis of patients with gastric cancer. TMEM92‐AS1 may also promote the secretion of G‐CSF by tumour cells to increase the level of neutrophils in the peripheral blood.